Implementation of the Family Hope Program (PKH) Policy on Family Welfare (A Study in Karang Desa, Pemenang Barat Village, Pemenang District, North Lombok Regency) - Diva Rahman; Yuliatin, Yuliatin; Sawaludin, Sawaludin (JURNAL PENDIDIKAN IPS, 2025)
Poverty remains a pressing issue in many regions of Indonesia, including North Lombok Regency, where poor families face limited access to health, education, and social welfare services. To address this, the government introduced the Family Hope Program (PKH), a conditional cash transfer aimed at reducing social vulnerability and improving the quality of life of poor households. This study aims to describe the implementation of the Family Hope Program (PKH) policy and its impact on family welfare in Dusun Karang, Pemenang Barat Village, Pemenang Subdistrict, North Lombok Regency. This research employs a qualitative descriptive approach. Data were collected through interviews, observations, and documentation. Research informants consisted of 10 Beneficiary Families (KPM), 1 PKH facilitator, and 1 village government official, selected using purposive sampling. Data analysis followed the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. Data validity was tested through technique triangulation, source triangulation, and time triangulation. The findings show that the implementation of the PKH policy in Dusun Karang has been carried out properly in accordance with Minister of Social Affairs Regulation (Permensos) No. 1 of 2018 and other supporting regulations. Seven policy components have been effectively implemented: routine health checks for pregnant women and toddlers (Article 7 letter a), minimum 85% school attendance for children (Article 7 letter b), nutrition counseling, immunization, and healthy living education through Family Development Sessions (FDS/P2K2 Module), education on the importance of schooling, elderly participation in social activities (Article 7 letter c), utilization of the Indonesian Health Card (KIS) through JKN-PBI integration (Presidential Regulation No. 82 of 2018), and home visits for the elderly (Permensos No. 5 of 2019 on ATENSI). However, integration with the Indonesia Smart Program (PIP) has not been optimally implemented. The program has had several positive impacts, including increased access to health and education services, strengthened social roles of the elderly, behavioral changes within families, and reduced household economic burdens. Thus, PKH functions not only as financial aid but also as a social development instrument that supports the transformation of family welfare at the village level.